Overcoming evasive resistance from vascular endothelial growth factor a inhibition in sarcomas by genetic or pharmacologic targeting of hypoxia‐inducible factor 1α. Issue 1 (26th June 2012) - Kim, Yeo‐Jung; Lee, Hae‐June; Kim, Tae‐Min; Eisinger‐Mathason, T.S. Karin; Zhang, Alexia Y.; Schmidt, Benjamin; Karl, Daniel L.; Nakazawa, Michael S.; Park, Peter J.; Simon, M. Celeste; Yoon, Sam S.
Abstract Increased levels of hypoxia and hypoxia‐inducible factor 1α (HIF‐1α) in human sarcomas correlate with tumor progression and radiation resistance. Prolonged antiangiogenic therapy of tumors not only delays tumor growth but may also increase hypoxia and HIF‐1α activity. In our recent clinical trial, treatment with the vascular endothelial growth factor A (VEGF‐A) antibody, bevacizumab, followed by a combination of bevacizumab and radiation led to near complete necrosis in nearly half of sarcomas. Gene Set Enrichment Analysis of microarrays from pretreatment biopsies found that the Gene Ontology category "Response to hypoxia" was upregulated in poor responders and that the hierarchical clustering based on 140 hypoxia‐responsive genes reliably separated poor responders from good responders. The most commonly used chemotherapeutic drug for sarcomas, doxorubicin (Dox), was recently found to block HIF‐1α binding to DNA at low metronomic doses. In four sarcoma cell lines, HIF‐1α shRNA or Dox at low concentrations blocked HIF‐1α induction of VEGF‐A by 84–97% and carbonic anhydrase 9 by 83–93%. HT1080 sarcoma xenografts had increased hypoxia and/or HIF‐1α activity with increasing tumor size and with anti‐VEGF receptor antibody (DC101) treatment. Combining DC101 with HIF‐1α shRNA or metronomic Dox had a synergistic effect in suppressing growth of HT1080 xenografts, at least in part via induction of tumor endothelial cell apoptosis. In conclusion, sarcomas respond to increased hypoxia by expressing HIF‐1α target genes that may promote resistance to antiangiogenic and other therapies. HIF‐1α inhibition blocks this evasive resistance and augments destruction of the tumor vasculature.